Father-Child Conflict and Chinese Adolescent Depression: A Moderated Mediation Model - Peng, Cong; Chen, Jianwen; Wu, Huifen; Liu, Yan; Liao, Youguo; Wu, Yuqin; Zheng, Xintong (Frontiers in Psychology, 2021)
To investigate the effects of father-child conflict and regulatory emotional self-efficacy (RESE) on Chinese adolescent depression, 654 middle-school students were measured. The results showed that: (1) Father-son conflict was significantly lower than father-daughter conflict, girls’ depression was significantly higher than that of boys, and boys’ RESE and self-efficacy in regulating negative emotions (NEG) were significantly higher than that for girls, but there was no significant difference between boys and girls in self-efficacy in expressing positive emotions (POS). (2) Father-child conflict was significantly positively associated with Chinese adolescent depression. Father-child conflict was negatively correlated with RESE, and its two dimensions. Both POS and NEG played a partial mediating role in the relationship between father-child conflict and adolescent depression. (3) Gender only regulated the relationship between NEG and adolescent depression. Compared to boys, girls are more affected by depression at the low level of NEG.